Etika Bisnis Dalam Perspektif Sunnah Nabi - Rozi Rozi (Jurnal Ilmiah Ekonomi Islam, 2023)
This paper aims to discuss business ethics from the perspective of the Sunna of the Prophet. This manuscript was written using a literature review approach. The results of the discussion show that in running a business, ethics is very important. The term business ethics originally appeared in the 1970s in America, 1980s in Europe, and 1990s in Asian countries. Even so, it should be noted that actually long before that, namely in the 14th century, the Prophet Muhammad SAW had introduced ethics in doing business. Interestingly, ethical issues have been introduced through the business activities that have been carried out. The business ethics that he applies in running a business are: honest, voluntary, not cheating, not dropping other people's businesses, free from usury practices, not hoarding goods, not monopolizing, prioritizing consumer satisfaction, not tyrannizing employees, maintaining trust, upholding values tolerance, always keeping promises, being generous, not forgetting the hereafter, being fair, and only selling quality products that are guaranteed to be halal.